Degradasi Lingkungan dalam Novel Teruslah Bodoh Jangan Pintar karya Tere Liye Kajian Ekologi Sastra - Anzila Khoirony; Darwin Effendi; Dian Nuzulia Armariena (Pusat riset dan Inovasi Nasional, 2025)
The purpose of of this research is to describe environmental degradation in the novel Teruslah Bodoh Jangan Pintar by Tere Liye using the ecological study of literary Grag Gerrard's ecological study of literature theory. This research is a descriptive qualitative research, in which data findings are in the form of quotations or dialog related to environmental degradation in the novel Teruslah Bodoh Jangan pintar by Tere Liye. Smart by Tere Liye. The results show that environmental degradation includes 6 (six) forms of environmental degradation in the novel. this novel, namely 10 pollution, 6 wilderness, 13 disasters, 12 dwellings, 4 animals and 8 earth. Meanwhile, 3 (three) efforts to overcome environmental degradation (environmental ethics) in this novel are 3 attitude of responsibility towards nature, 4 attitudes of love and care for nature and 1 attitude of not disturbing the life of nature. Among these, the most dominant form of degradation found in the novel is natural disasters, as shown through various excerpts and dialogues. This study is also relevant to academic learning as it enriches students' textual understanding while fostering social awareness, moral responsibility, and environmental concern.